Coastal currents in the Eastern Gulf of Tehuantepec from coastal altimetry - Salazar- Ceciliano, Juan Pablo (2018)
we study the seasonal and interannual variability of the coastal currents along the eastern shelf of the Gulf of Tehuantepec. We use sea level from coastal altimetry distributed by the Centre de Topographie des Oceans et de l’Hydrosphe`re (Toulouse, France). Local validation using tide gauge and hydrographic data indicates that this coastal product measures well the seasonal and interannual scales along this tropical coastline. Long (12 years) time series of altimetry-derived currents, 39–57 km from the coast, reveal new details of the seasonal cycle: currents flow poleward from October to February and equatorward from April to August. Spectral analysis reveals that mesoscale processes are at least as energetic as the seasonal mean. The combination of both determines to a large extent the seasonal and interannual variability of the coastal currents.